Yes and No on What to Do about Radio Free Europe - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. This report was assigned the following topical and geographical subject headings by the RFE/RL: Country Series: Poland The principal RFE/RL contributor to this report was: Szelag, Jan